Economic Cooperation of the Bukhara People`s Soviet Republic with Sweden - Nuridinov Turdali Kambarovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article covers the history of economic relations with Sweden`s “Atlas-Dizel” firm in 1920-1924. The BPSR`s трансCaucasian trade office cooperated with the “Atlas-Dizel” firm for electrification in Bukhara. Under pressure from Soviet foreign trade organizations, trade relations ended.